Postnukleare Handlungstheorie: Ein soziologisches Akteurmodell für Cyborgs - Compagna, Diego (transcript, 2015)
Against the background of a critical reconstruction of sociological theory formation, Diego Compagna develops and actor model for cyborgs that especially draws on the difference between subject and actor. The scientifically inspired reconstruction and the actor model derived from it also point out that sociology always (re)produces inequality – by promoting a reification of the social actor as a »human« or »phenomenologically determinable« subject which can never occur as a neutral entity.